The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/fsn3.239
|View full text |Cite
|
Sign up to set email alerts
|

Development of cereal‐based functional food using cereal‐mix substrate fermented with probiotic strain – Pichia kudriavzevii OG32

Abstract: Probiotic strains contribute to the functionality of foods during fermentation. In this present work, cereal‐mix was fermented with probiotic Pichia kudriavzevii OG32. Selected fermentation parameters and functional properties of the product were determined. The growth of Pichia kudriavzevii OG32 was supported by the cereal‐mix containing 1% salt and 0.2% red chili powder to counts of between 7.46 and 8.22 Log10 cfu/mL within 24 h. Pichia kudriavzevii OG32 increased the viscosity of cereal‐mix with the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The food was prepared every other day using activated Pichia kudriavzevii OG32 as described by Ogunremi et al (2015).…”
Section: Preparation Of Cereal-based Functional Food (Cbff)mentioning
confidence: 99%
See 1 more Smart Citation
“…The food was prepared every other day using activated Pichia kudriavzevii OG32 as described by Ogunremi et al (2015).…”
Section: Preparation Of Cereal-based Functional Food (Cbff)mentioning
confidence: 99%
“…In an earlier study by Ogunremi, Agrawal, and Sanni (2015), we suggested the suitability of cereal-based matrix as carrier for a probiotic yeast strain. Therefore, the objective of this present study was to investigate the effects of cereals-mix fermented with probiotic Pichia kudriavzevii OG32 on the levels of plasma antioxidant markers in rats fed a high cholesterol diet and the levels of lipids in their serum and liver.…”
Section: Introductionmentioning
confidence: 98%
“…Besides prebiotics and probiotics (Cui et al, 2013), the symbiotic relationship between immune cells and gut microbiota (Yamamoto and Matsumoto, 2016) in the prevention of this disease also needs to be highlighted. Foods with the above mentioned benefits are directly associated with the prevention of diseases or are able to beneficially contribute to the individual's health, being called functional foods (Oliveira et al, 2006(Oliveira et al, , 2007Ogunremi et al, 2015). Among commercialized probiotic products, we can refer to the industrialized product Activia ® (Danone), which is consumed worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…T.reesei [12], F. venenatum [13], and Mucor circinelloides [14] are listed generally recognized as safe (GRAS) strains, while enzymes and pullulan from A. pullulans are GRAS products [15,16]. The yeast Pichia kudriavzevii was also included due to its potential probiotic effects [17]. Since the cold press and hexane extraction are the two commercialized methods of oil extraction, meals from both processes were evaluated.…”
Section: Introductionmentioning
confidence: 99%